2018
DOI: 10.1186/s12885-018-4711-0
|View full text |Cite
|
Sign up to set email alerts
|

A suppressive role of guanine nucleotide-binding protein subunit beta-4 inhibited by DNA methylation in the growth of anti-estrogen resistant breast cancer cells

Abstract: BackgroundBreast cancer is the most common malignancy in women worldwide. Although the endocrine therapy that targets estrogen receptor α (ERα) signaling has been well established as an effective adjuvant treatment for patients with ERα-positive breast cancers, long-term exposure may eventually lead to the development of acquired resistance to the anti-estrogen drugs, such as fulvestrant and tamoxifen. A better understanding of the mechanisms underlying antiestrogen resistance and identification of the key mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…These results indicated that DNA methylation patterns were different between the two groups of cells. Moreover, many studies have shown that the methylation patterns of breast cancer resistant cells and sensitive cells are different [20][21][22]. This information also proves the reliability of our research results.…”
Section: Different Dna Methylation Patterns Between Two Types Of Breasupporting
confidence: 86%
“…These results indicated that DNA methylation patterns were different between the two groups of cells. Moreover, many studies have shown that the methylation patterns of breast cancer resistant cells and sensitive cells are different [20][21][22]. This information also proves the reliability of our research results.…”
Section: Different Dna Methylation Patterns Between Two Types Of Breasupporting
confidence: 86%
“…Compared to the MCF-7 parental cell line the DNA methylation pattern is different in FULV-R MCF-7 sublines (33,189,207,208). Both altered hyper-and hypomethylation of promoters and enhancers were found to coincide with FULV resistance.…”
Section: Dna Methylationmentioning
confidence: 92%
“…Both altered hyper- and hypomethylation of promoters and enhancers were found to coincide with FULV resistance. Hypermethylation of promoters in the anti-estrogen-resistant sublines was linked to either a higher expression of DNA methyltransferase (DNMT) 3B or DNMT1 ( 207 , 209 ). In FULV-R MCF-7 cells, promoter A of the esr1 gene is one of the hypermethylated promoters giving rise to strongly reduced ERα expression ( 208 ).…”
Section: Chromatin Accessibilitymentioning
confidence: 99%
“…It is noteworthy that “Pathways in cancer” was the most enriched pathway in which Ras-related C3 botulinum toxin substrate 2 (RAC2), guanine nucleotide-binding protein subunit beta-4 (GNB4), prostaglandin E2 receptor EP4 subtype (PTGER4), G1/S-specific cyclin-E2 (CCNE2), Frizzled-8 (FZD8), transforming growth factor beta-3 (TGFB3), laminin subunit alpha-2 (LAMA2), glutathione S-transferase Mu 1 (GSTM1), and matrix metalloproteinase-2 (MMP2) are involved. Though RAC2 ( 20 ), GNB4 ( 21 ), PTGER4 ( 22 , 23 ), CCNE2 ( 24 ), FZD8 ( 25 ), TGFB3 ( 26 ), LAMA2 ( 27 ), and GSTM1 ( 28 , 29 ) have been reported to be regulated by methylation in multiple cancers, very little is known about the regulatory mechanisms by which methylation is involved in HCC. Moreover, the term “Hepatocellular carcinoma” is enriched with FZD8, ribosomal protein S6 kinase alpha-6 (PRSAKA6), TGFB3 and GSTM1.…”
Section: Discussionmentioning
confidence: 99%